Semantic Analysis: Japanese Idiom (Kanyouku) Using Part of Body Lexemes - Soidi, Orestis; Komarudin, Mochamad Arief (Vocational College of Diponegoro University, 2023)
The purpose of this study is to describe the idiomatic and lexical meanings of Japanese idioms using part of body lexemes. The technique utilized in this study is perusing and note taking strategies. There are 78 idioms found in the data source which are divided into several meaning or meaning classifications, 1) Idioms that show feelings and emotions; 2) Idioms related to body, character, and attitude; 3) Idioms that indicate action, or activity; 4) Idioms that indicate a state, degree, or level of value; and 5) Idioms that indicate local life, culture, and society. It can be concluded that based on the results of the analysis and discussion of Japanese idioms containing body lexemes, Japanese idioms using body part lexemes are still often used in daily life.